Social Work Practice Intervention in Dealing with Juvenile Delinquency Problems: Intervensi Praktik Pekerjaan Sosial dalam Menangani Permasalahan Kenakalan Remaja - Nurwahyuliningsih, Eka (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This writing aims to find out the interventions that will be carried out by social workers as professionals in providing assistance to children who experience juvenile delinquency problems. Nowadays, juvenile delinquency is increasingly prevalent and has become an important concern for the community and the government. The development of the times, such as advances in technology and information, urbanization, and changes in family parenting, contribute to influencing adolescent behavior. This research uses a literature study as a research approach, conducted by reviewing 34 reference sources consisting of news articles, scientific articles, and books that are in accordance with the chosen problem topic. Through content analysis, this study shows that there are four forms of juvenile delinquency including juvenile delinquency that causes physical harm to others, juvenile delinquency that causes material harm, social delinquency that does not cause harm to others, and delinquency that denies status. Being part of social problems, juvenile delinquency is one of the main focuses of social workers because of its wide impact on individuals, families and society. Social workers are oriented towards dealing with this problem using various approaches and methods oriented towards recovery and prevention. The stages of the intervention process provided by social workers consist of five stages, namely the initial approach, the assessment stage, the planning and contracting stage, the intervention stage, and evaluation and termination. Meanwhile, the factors that cause juvenile delinquency can be seen from parenting, the influence of the social environment, advances in technology, and information. Interventions carried out by social workers are holistic, integrated, and community-based, so that they are able to improve the social functions of the target group in order to experience better changes.